Mechanisms and Consequences of Partial Migration in Insects - Menz, Myles H. M.; Reynolds, Don R.; Gao, Boya; Hu, Gao; Chapman, Jason W.; Wotton, Karl R. (Frontiers in Ecology and Evolution, 2019)
Partial migration, where a proportion of a population migrates, while other individuals remain resident, is widespread across most migratory lineages. However, the mechanisms driving individual differences in migratory tendency are still relatively poorly understood in most taxa, but may be influenced by morphological, physiological and behavioral traits, controlled by phenotypic plasticity and the underlying genetic complex. Insects differ from vertebrates in that partial migration is often associated with pronounced morphological differences between migratory and resident phenotypes, such as wing presence or length. In contrast, the mechanisms influencing migratory tendency in wing-monomorphic insects is less clear. Insects are the most abundant and diverse group of terrestrial migrants, with trillions of animals moving across the globe annually, and understanding the drivers and extent of partial migration across populations will have considerable implications for ecosystem services, such as the management of pests and the conservation of threatened or beneficial species. Here we present an overview of our current but incomplete knowledge of partial migration in insects. We discuss the factors that lead to the maintenance of partial migration within populations, and the conditions that may influence individual decision making, particularly in the context of individual fitness and reproductive tradeoffs. Finally, we highlight current gaps in knowledge and areas of future research that should prove fruitful in understanding the ecological and evolutionary drivers, and consequences of partial migration in insects.